1967
DOI: 10.1042/bj1040524
|View full text |Cite
|
Sign up to set email alerts
|

Control of glycolysis in cerebral cortex slices

Abstract: 1. Intracellular concentrations of intermediates and cofactors of glycolysis were measured in guinea-pig cerebral cortex slices incubated under varying conditions. 2. Comparison of mass-action ratios with apparent equilibrium constants for the reactions of glycolysis showed that hexokinase, phosphofructokinase and pyruvate kinase catalyse reactions generally far from equilibrium, whereas phosphoglucose isomerase, aldolase, phosphoglycerate kinase, phosphoglycerate mutase, enolase, adenlyate kinase and creatine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
1

Year Published

1970
1970
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(46 citation statements)
references
References 29 publications
4
40
1
1
Order By: Relevance
“…Indeed, earlier suggestions (58,59) have been made that an association of G3PD and PGK with membranes may denote a separate ATP-generating pool for membrane-bound ATP-dependent processes and that a G3PD and aldolase complex may be involved as initiators of energy production (35). Of importance is the finding that G3PD is a key enzyme involved in control of glycolysis in cerebral cortex slices (60). Recently, Han et al (61) found that the triadic junction of skeletal muscle contains a compartmentalized reaction sequence of four glycolytic enzymes active in the synthesis of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, earlier suggestions (58,59) have been made that an association of G3PD and PGK with membranes may denote a separate ATP-generating pool for membrane-bound ATP-dependent processes and that a G3PD and aldolase complex may be involved as initiators of energy production (35). Of importance is the finding that G3PD is a key enzyme involved in control of glycolysis in cerebral cortex slices (60). Recently, Han et al (61) found that the triadic junction of skeletal muscle contains a compartmentalized reaction sequence of four glycolytic enzymes active in the synthesis of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Although one naturally must be circumspect in this type of estimation, it does signify possible biological relevance. Assuming that DNA damage is proportional to Glc-6-P concentration (4) and that the intracellular Glc-6-P concentration is 0.25 mM (19), then a 4.2 logarithm inactivation (25 days for 200 mM Glc-6-P, Fig. 1) for the amp gene indicates that the human genome on the average would suffer 2.7 Glc-6-P "hits" per day.…”
Section: Discussionmentioning
confidence: 99%
“…An additional contributing factor explaining the elevation of PEP may also include the possibility that enzymatic regulation was operating on pyruvate kinase. which potentially may be one ratelimiting glycolytic enzyme in cerebral (25,33) and other (6) tissues.…”
Section: Cerebral Amino Acid a N D Related Intermediatesmentioning
confidence: 99%